Analysis of the frequency of EGFR, KRAS and ALK mutations in patients with lung adenocarcinoma in Croatia - Brcic, Luka (Diagn Pathol, 2016)
BACKGROUND: Many studies have been published on the mutational status of patients with lung adenocarcinomas, and great population-based variability in mutation frequencies has been reported. The main objective of the present study was to analyze the EGFR, KRAS and ALK mutation status in a representative cohort of patients in Croatia with lung adenocarcinomas and to correlate the mutational status with clinical data. METHODS: All patients who were newly diagnosed within 6 months with histologically proven primary lung adenocarcinomas were included. Mutational analyses for EGFR and KRAS mutations were performed in a cobas z 480 analyzer. ALK immunohistochemistry was performed using the D5F3 clone on Benchmark XT instrument. Clinical data were obtained from the medical records. RESULTS: Of the 324 patients, 59.9 % were male. At the time of diagnosis, the patients ranged in age range from 35 to 88 years (median 63 years). Most of the patients were current smokers or former smokers (77.2 %). EGFR mutations were found in 15.7 % of the patients, and of these mutations, exon 19 deletion was the most common (45.1 %). KRAS mutations were present in 34.9 % of the patients, while 4.1 % of patients were ALK-positive. The statistical significance of the presence of mutations was detected for both gender and smoking. CONCLUSION: The detected mutation rates demonstrated a slightly higher prevalence of KRAS mutations, but not a higher prevalence of EGFR mutations or ALK gene rearrangement, in comparison with the rates found in other European countries. EGFR and ALK mutational status showed a statistically significant correlation with gender as well as with smoking, while KRAS mutation status showed a statistically significant correlation only with smoking. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13000-016-0544-9) contains supplementary material, which is available to authorized users.